SPECT and PET Imaging of Meningiomas - Varvara Valotassiou; Anastasia Leondi; George Angelidis; Dimitrios Psimadas; Panagiotis Georgoulias (The Scientific World Journal)
Meningiomas arise from the meningothelial cells of the arachnoid membranes. They are the most common primary intracranial neoplasms and represent about 20% of all intracranial tumors. They are usually diagnosed after the third decade of life and they are more frequent in women than in men. According to the World Health Organization (WHO) criteria, meningiomas can be classified into grade I meningiomas, which are benign, grade II (atypical) and grade III (anaplastic) meningiomas, which have a much more aggressive clinical behaviour. Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) are routinely used in the diagnostic workup of patients with meningiomas. Molecular Nuclear Medicine Imaging with Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET) could provide complementary information to CT and MRI. Various SPECT and PET tracers may provide information about cellular processes and biological characteristics of meningiomas. Therefore, SPECT and PET imaging could be used for the preoperative noninvasive diagnosis and differential diagnosis of meningiomas, prediction of tumor grade and tumor recurrence, response to treatment, target volume delineation for radiation therapy planning, and distinction between residual or recurrent tumour from scar tissue.